2017
DOI: 10.3329/dujbs.v26i1.46346
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and fatty acid profile of Nile tilapia Oreochromis niloticus (Linnaeus, 1758) fed with different phytoplankton

Abstract: The effect of different phytoplankton species on growth, survival and fatty acids composition of Nile tilapia (Oreochromis niloticus) was evaluated for 24 weeks. Treatment-1 was fed with commercial feed as Control, treatment-2 was fed with Spirulina platensis, treatment-3 was fed with Chlorella vulgaris and treatment-4 was fed with mixed phytoplankton (Chlorella vulgaris, Spirulina platensis, Azolla pinnata and Pistia stratiotes). The condition factor of fish found in treatment-3 with Chlorella vulgaris (1.73 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The mean value of SGR in T 1 and T 2 were 6.27 ± 3.27 and 6.26 ±3.83, respectively which were higher than the result of Hossain et al 2017.…”
Section: Discussionmentioning
confidence: 55%
“…The mean value of SGR in T 1 and T 2 were 6.27 ± 3.27 and 6.26 ±3.83, respectively which were higher than the result of Hossain et al 2017.…”
Section: Discussionmentioning
confidence: 55%
“…Mixing by aeration can minimize organic matter accumulation that may increase BOD, reduce the density of algal blooms that can lead to oxygen depletion and fish health issues, and shift the composition of algae blooms that may lead to flavor issues in finfish (Hargreaves, 2003). Hossain et al (2017) indicated that the highest value of condition factor (1.73 ± 0.02) was recorded in tilapia fed on Chlorella vulgaris and the lowest value (1.56 ± 0.02) of fish fed with commercial feed (control). In the current investigation the estimated condition factor for O. niloticus was high in aerated ponds which increase conversion ratio of this fish.…”
Section: Discussionmentioning
confidence: 97%
“…These outcomes confirm similar findings across the literature on spirulina trials as feed in the aquaculture sector, mostly in Asia. This includes experiments on growth performance, survival rate, fatty acid profiles, and fecundity of Nile tilapia (O. niloticus) conducted in Bangladesh (Hossain, 2017). In Japan, it has been found that tilapia fed solely raw spirulina has a high flesh quality (Lu et al, 2003).…”
Section: Discussion -Trial Outcomes and Potentials For Enhanced Livel...mentioning
confidence: 99%